2020
DOI: 10.2196/20797
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User Needs in the Development of a Virtual Reality–Based Advanced Life Support Training Platform: Exploratory Usability Study

Abstract: Background Traditional methods of delivering Advanced Life Support (ALS) training and reaccreditation are resource-intensive and costly. Interactive simulations and gameplay using virtual reality (VR) technology can complement traditional training processes as a cost-effective, engaging, and flexible training tool. Objective This exploratory study aimed to determine the specific user needs of clinicians engaging with a new interactive VR ALS simulation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…To the best of our knowledge, this is the first time that such a VR simulation platform has been developed explicitly for use in a cardiac arrest scenario after cardiac surgery. Although future refinements of this concept are inevitable, we believe that the CPVR-sim will be a successful method that will help to overcome difficult challenges, including the infrequent incidence of resternotomy after cardiac surgery, accessibility, and costs of clinical training [ 25 ]. We observed that the expert and novice opinions were generally positive regarding the face validity and content validity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first time that such a VR simulation platform has been developed explicitly for use in a cardiac arrest scenario after cardiac surgery. Although future refinements of this concept are inevitable, we believe that the CPVR-sim will be a successful method that will help to overcome difficult challenges, including the infrequent incidence of resternotomy after cardiac surgery, accessibility, and costs of clinical training [ 25 ]. We observed that the expert and novice opinions were generally positive regarding the face validity and content validity.…”
Section: Discussionmentioning
confidence: 99%
“…This active involvement could be due to the elaborate simulation and multiple actions the user has to perform. This immersive and realistic VR environment facilitates memorizing stepwise procedures more efficiently [ 25 ]. Additionally, our results showed that frequent practice and increased exposure in the CPVR-sim is valuable since it refreshes the knowledge and gives the clinician more confidence in taking the lead in future situations, which is in line with previous studies [ 8 , 9 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the rapid innovation that recent events have been a catalyst for, the authors have developed several innovative VR based applications to supplement face-to-face education in the health service. VR based applications supporting Advanced Life Support (ALS) leadership called ALS-SimVR ( 5 , 6 ), Code Black identification and response training and a tool for reflective practice in a variety of clinical and non-clinical settings are all in varying stages of development within the LHD.…”
Section: Vr In Clinical Educationmentioning
confidence: 99%
“…To date, VR has been used to support burn victims [ 4 , 5 ], as exposure therapy for phobias [ 6 ], in the management of traumatic brain injury [ 7 ], and to increase physical activity undertaken by members of the general public [ 2 , 8 ]. In addition to being used to support health care consumers, VR has been used to enhance medical training by augmenting existing approaches to surgical skills training [ 9 ], advanced life support training [ 10 ], and for developing empathy skills [ 11 ].…”
Section: Introductionmentioning
confidence: 99%